Asuhan Kebidanan Komprehensif Pada Ny. D Dengan Resiko Tinggi : (Studi Kasus Terhadap Ny D Di Puskesmas Pangkah Kabupaten Tegal Tahun 2023) - Islakhul Zachro; Istiqomah Dwi Andari; Riska Arsita (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
In 2022, Pangkah Public Health Center in Tegal Regency recorded 2 cases of maternal deaths, attributed to hemorrhage and umbilical cord embolism. Data obtained from the health center in 2023 revealed a total of 874 pregnant women, with 475 categorized as high-risk. Risk factors included maternal age <20 years (17 cases), maternal age >35 years (133 cases), interpregnancy interval <2 years (31 cases), nutritional problems (109 cases), anemia (50 cases), presence of more than 5 children (17 cases), and others (118 cases). Among high-risk pregnancies, women aged >35 years and those falling into the